PROMOSI KESEHATAN TENTANG PEMBERIAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA PEMBUAT BATU BATA - Rosita Ginting; Irmayani Irmayani; Anggi Isnani Parinduri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
The number of work accidents in workers continues to increase from year to year. One of the causes of work accidents is the lack of awareness of workers to use PPE at work. This paper aims to provide health promotion to brick-making workers about the importance of using PPE when working. The method of implementing this activity is through observation and providing health education about the use of PPE. From the results of the activities carried out, the workers enthusiastically welcomed this activity. It is hoped that with this activity there will be an increase in the compliance of brick-making workers in using PPE at work